1998
DOI: 10.1007/s004420050643
|View full text |Cite
|
Sign up to set email alerts
|

Distance-dependence in herbivory and foliar condition for juvenile Shorea trees in Bornean dipterocarp rain forest

Abstract: We assessed density- and distance-dependence in herbivore effects and juvenile condition for four species of Shorea, the most speciose genus in the dominant canopy family of southeast Asian rain forest trees (Dipterocarpaceae). Herbivore damage was quantified as partial leaf loss on young leaves, and whole plant foliar condition as the product of the fraction of leaf nodes containing leaves and the fraction of tissue remaining on extant leaves. Adults of the four species were centers of high total, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 56 publications
5
42
0
1
Order By: Relevance
“…Although many studies have documented negative eVects of insect herbivores on seedlings, surprisingly few have done so in the context of the Janzen-Connell mechanism in tropical forests (Clark and Clark 1985;Blundell and Peart 1998;Massey et al 2006). These found evidence for species-speciWc increases in leaf damage with either proximity to parent trees and/or immediate seedling density, but the insect herbivores implicated were not known, nor was their degree of host specialisation.…”
Section: Discussionmentioning
confidence: 98%
“…Although many studies have documented negative eVects of insect herbivores on seedlings, surprisingly few have done so in the context of the Janzen-Connell mechanism in tropical forests (Clark and Clark 1985;Blundell and Peart 1998;Massey et al 2006). These found evidence for species-speciWc increases in leaf damage with either proximity to parent trees and/or immediate seedling density, but the insect herbivores implicated were not known, nor was their degree of host specialisation.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the many tests of the Janzen-Connell hypothesis have yielded mixed results. For example, Blundell and Peart (1998) …”
Section: Discussionmentioning
confidence: 99%
“…A few other studies have found distancedependent effects of herbivory using methodologies that focus on only a few adult trees (Clark & Clark 1985, Blundell & Peart 1998, Barone 2000. Unlike those studies, here I focused on density-dependence and used a methodology based on analysis of spatial dynamics at the population scale.…”
Section: Discussionmentioning
confidence: 99%